PENGARUH LINGKUNGAN SEKOLAH DAN PERAN ORANG TUA TERHADAP HASIL BELAJAR SISWA DI SMK N 1 LOLAYAN - Adji, Putri Nadia Anjelia; Makaliwe, Niny; Wantah, Edwin; Dame, Joubert (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the influence of the School Environment on Learning Outcomes at SMK N 1 Lolayan, to determine the Role of Parents on Learning Outcomes at SMK N 1 Lolayan, and to determine the influence of the School Environment and the Role of Parents together on Learning Outcomes at SMK N 1 Lolayan. The research method used is the Survey research method, the main source of data and information is obtained from respondents as research samples using questionnaires or surveys as data collection instruments. The results of the study show that the School Environment variable (X_1) has a positive or significant influence on the Learning Outcome variable (Y) at SMK N 1 Lolayan, the Parental Role variable (X_2) has a positive or significant influence on the Learning Outcome variable (Y) at SMK N 1 Lolayan, and the School Environment variable (X_1), the Parental Role variable (X_2) together have a positive or significant influence on the Learning Outcome variable (Y) at SMK N 1 Lolayan. Keywords: School Environment, Role of Parents, Learning Outcomes